(untitled) (Research, Society and Development, 2025)
This study is an experience report on the application of functional training (FT) in children (6-12 years old) enrolled in tennis lessons in Manaus over a period of 1 year. The objective was to analyze the contribution of this methodology to the development of young tennis players, combining practical experience with scientific evidence. The FT sessions, held twice a week, focused on strength, agility, balance, and coordination.The analysis of results, based on observations and reports, revealed significant gains in four categories: motor performance (greater speed, precision, and body control); technical performance in tennis (improved stroke precision, serves, and postural stability); engagement and motivation (enthusiasm, social interaction, and adherence to practice, driven by the playful nature of FT); and injury prevention and body awareness (core strengthening and spontaneous posture adjustments). It was concluded that FT is an effective and enjoyable pedagogical resource in sports initiation for tennis, promoting the athlete’s integral development by integrating physical, technical, motivational, and safety progress.